Draft Sixth Five-Year Plan 1980-85 and Draft Annual Plan 1981-82 (Submitted to Planning Commission in November, 1980) Himachal Pradesh - Planning Commission (Planning Commission, 1980)
The above table reveals that the real growth of income in Himachal Pradesh during the 1970—79 period Was at a rate of 1.1 per cent per annum. But this per capita average income growth rate does not reflect the genuine welfare of growth aspect unless we simultaneously know the distribution pattern. Thus the relation between output, working force and population has to be viewed in the correct perspective to measure economic development of a particular region.
Planning Department, Himachal Pradesh